2016
DOI: 10.1177/0363546516652894
|View full text |Cite
|
Sign up to set email alerts
|

Trochleoplasty as a Solitary Treatment for Recurrent Patellar Dislocation Results in Good Clinical Outcome in Adolescents

Abstract: In this study, trochleoplasty as a solitary treatment for recurrent patellofemoral dislocations in patients with trochlear dysplasia resulted in good clinical outcomes if severe torsional and axial malalignment was excluded. Kujala and Lysholm scores increased postoperatively, as well as subjective International Knee Documentation Committee assessment of outcomes, activity level, and overall satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 46 publications
(45 reference statements)
0
62
0
Order By: Relevance
“…The salient finding of the present study is that the mean TA showed a significant positive correlation with Dejour type from B to D. Many studies have recommended that severe trochlear dysplasia should be corrected by a tracheloplasty procedure for long-term patellar stability [ 15 19 ]. Several investigators have deemed severe trochlear dysplasia to be a significant negative prognostic risk factor for other procedures performed without managing trochlear dysplasia [ 20 ].…”
Section: Discussionmentioning
confidence: 49%
“…The salient finding of the present study is that the mean TA showed a significant positive correlation with Dejour type from B to D. Many studies have recommended that severe trochlear dysplasia should be corrected by a tracheloplasty procedure for long-term patellar stability [ 15 19 ]. Several investigators have deemed severe trochlear dysplasia to be a significant negative prognostic risk factor for other procedures performed without managing trochlear dysplasia [ 20 ].…”
Section: Discussionmentioning
confidence: 49%
“…Today, open trochleoplasty techniques include (1) lateral-facet elevation trochleoplasty, which deepens the trochlear groove by elevating the lateral facet of the femoral condyle and was first reported by Albee; (2) sulcus-deepening trochleoplasty, which includes 2 types, Dejour sulcus deepening (“Lyon procedure”) with a thick osteochondral flap and V-shaped osteotomy 10 and Bereiter-Gautier subchondral sulcus deepening with a thin osteochondral flap and U-shaped osteotomy 11 ; and (3) recession wedge trochleoplasty. 12 The first 2 trochleoplasty procedures have been the most commonly used techniques in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Trochleoplasty, as a solitary or concomitant treatment for recurrent patellar instability, is associated with significantly improved stability and function. 4 , 11 , 13 Nevertheless, trochleoplasty is still a daunting procedure for surgeons because of its multiple and gloomy complications. A 15-year follow-up study of trochleoplasty reported that 20% of patients had total failure and 23% of patients identified postoperative stiffness at less than 90° of flexion.…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to various complications. Camathias et al [18] described recurrent patellar dislocations associated with isolated trochleoplasty outcomes. Precise planning is needed before the surgery to avoid uncommon complications, such as articular surface damages, overcorrection, and recurrent instability [11].…”
Section: Discussionmentioning
confidence: 99%